Pengaruh Investasi, Pertumbuhan Ekonomi, Jumlah Penduduk Terhadap Tingkat Pengangguran Di Kabupaten/Kota Kalimantan Barat - B01110027, FETRA ARIESTA (Jurnal Curvanomic, 2016)
This study aims to identify and analyze the influence of Investment, Economic Growth andPopulation against Unemployment in the District/City of West Kalimantan 2009-2013 period.This research uses descriptive quantitative method by using secondary data, panel data (cross section andtime series), obtained from the office of the Central Statistics Agency of West Kalimantan. The analyticaltool used to process the data that is used Eviews 6. Observation of the data as much as 60 of the 12 districts/ municipalities in West Kalimantan during the period 2009 through 2013.Multiple regression results of this study indicate that the variable investment and no significant positiveeffect on the 0,15 and probability 0.3284 > 0.05 . Variable Growth and significant negative effect on theunemployment -0.30 and a probability of 0.0381 < 0.05. And variable Population significant negativeeffect on the unemployment -0,177 and a probability of 0.0626 < 0.10. The test results simultaneouslyobtained Fstatistik value of 7,212156 with a value prob (Fstatistik)of 0.00000 is smaller than 0.05 (probability < 0.05 ). This means the unemployment rate is influenced by the Investment, Economic Growthand Population together .Keywords: Investment, Economic Growth, Population, Unemployment Rate